Tanggapan Followers Mengenai Diskriminasi Kaum Marjinal dalam Laporan Remotivi - Farhan Aprilian Ruslan; kiki Zakiah darmawan (UNISBA Press, 2023)
Abstract. Media owners take advantage of technological advances. Social media is a means to disseminate news and other information to the public. The existence of social media causes the spread of news quickly and has negative or positive effects. This makes audiences more selective in choosing the media they access. Presenting the issue of marginalized discrimination attracts attention for researchers. Marginalization is a phenomenon of imbalance in obtaining opportunities in economic, social, and educational aspects by a group of people. Unisba Journalism students are active users of social media. They chose Remotivi as a trusted medium. Not only do they actively use Twitter and access Remotivi, they are also active in writing comments in the column provided by Remotivi. The purpose of this study was to find out the hypothetical position of the Unisba Fikom Journalistic Students regarding Remotivi's broadcast, namely discrimination against marginalized communities. The method used in this research is qualitative with Stuart Hall's reception analysis approach and the theory used is Stuart Hall's meaning theory. The results of this study show that how the reception and mortgage positions of UNISBA journalism students are after watching Remotivi's shows. Media owners take advantage of technological advances. Social media is a means to disseminate news and other information to the public. The existence of social media causes the spread of news quickly and has negative or positive effects. This makes audiences more selective in choosing the media they access. Presenting the issue of marginalized discrimination attracts attention for researchers. Marginalization is a phenomenon of imbalance in obtaining opportunities in economic, social, and educational aspects by a group of people. Unisba Journalism students are active users of social media. They chose Remotivi as a trusted medium. Not only do they actively use Twitter and access Remotivi, they are also active in writing comments in the column provided by Remotivi. The purpose of this study was to find out the hypothetical position of the Unisba Fikom Journalistic Students regarding Remotivi's broadcast, namely discrimination against marginalized communities. The method used in this research is qualitative with Stuart Hall's reception analysis approach and the theory used is Stuart Hall's meaning theory. The results of this study show that how the reception and mortgage positions of UNISBA journalism students are after watching Remotivi's shows. Abstrak. Keberadaan media sosial tersebut menimbulkan tersebarluasnya berita secara cepat dan menimbulkan efek negative ataupun positif. Hal tersebut membuat khalayak lebih selektif dalam memilih media yang diaksesnya. Menampilkan isu tentang diskriminasi kaum marjinal menarik perhatian bagi peneliti Marjinalisasi adalah fenomena ketidakseimbangan dalam memperoleh peluang dalam aspek ekonomi, social, dan pendidikan oleh sekumpulan masyarakat. Mahasiswa Jurnalistik unisba merupakan pengguna aktif media sosial. Mereka memilih Remotivi sebagai media yang terpercaya. Tujuan penelitian ini adalah untuk mengetahui posisi hipotekal Mahasiswa Jurnalistik Fikom Unisba mengenai tayangan milik remotivi yaitu diskriminasi masyrakat marjinal. Metode yang digunakan dalam penelitian ini yaitu kualitatif dengan pendeketan analisis resepsi Stuart Hall dan teori yang digunakan adalah teori pemaknaan Stuart Hall. Hasil penelitian ini menunjukan bahwa bagaimana resepsi dan posisi hipotekal mahasiswa jurnalistik unisba setelah menonton tayangan milik remotivi.